Optimal cooling configurations for quantum information processing at milli-kelvin temperatures. (September 2022) - Poole, T.; Marsh, T.; Matthews, A.J.
Highlights: Cooling capacity requirements for quantum information processing are increasing. Efficient systems provide direct cooling capacity where it is needed. Significant improvements in available cooling capacity are possible at the cold plate. Abstract: So called quantum supremacy has been demonstrated by at least two groups utilising < 100 physical superconducting qubits cooled to milli-kelvin temperatures. It is acknowledged that scaling these efforts to fault-tolerant, general purpose quantum computers will require very many more logical qubits, each formed from several physical ones. Addressing and control of these qubits is an area of active research, but it is likely that increased cooling capacities, particularly at the lowest temperatures, will be a requirement for the realisation of systems beyond noisy intermediate-scale quantum processors. Here we demonstrate a method by which significantly increased cooling power at temperatures ∼ 200 mK can be generated without impacting on the performance of an adjacent stage providing cooling power at temperatures ∼ 20 mK.